Um estudo de caso com uma criança cega e uma vidente (gêmeas idênticas): habilidades sociais das crianças, crenças e práticas educativas da mãe - Costa, Carolina Severino Lopes da (Universidade Federal de São Carlos, 2005)
The repertoire of social skills of blind and sighted children can be different from each other, inasmuch as the absence of the sense of sight prevents the blind children from using the same resources as those commonly used by the sighted ones, for example the visual imitation in the process of learning social skills and behaviors. The area of Social Skills Training (SST) was the theoretical and practical reference for this study, whose general aim was to describe and characterize the social performances of two identical twins aged ten years old: Célia, who is blind; and Virna, who is sighted. In addition, the beliefs and educational practices of their mother, who is their main caregiver, were identified. The data were obtained by conducting an interview with the mother as well as by filming the children during free situations. A transcript was made of the mother s answers to the questions from the interview script, and then the content was analyzed by theme. According to a protocol for observing the free situations, the films were assessed so that the children s performances enabled to infer the categories of social skills. The results showed that the mother considers that Virna is more independent to perform certain activities, while Célia requires more care and attention, besides being more subject to restrictions. The results also showed that the sighted child presented a wider and more refined repertoire of social skills in relation to her sister. From the data, it is possible to conclude that blind and sighted children have distinct social skills repertories, and the existing differences can be related to the blind variable as well as to the differences in the way the caretaker stimulates the children. Therefore, it is considered important to plan programs aiming to maximize the social development of visually impaired children, including social skills training and advices for the caregivers.
A study of case with one blind and one sighted child (identicals twins: children s social skills, mother s beliefs and educative pratices.
Keywords: Educação especial estudantes cegos; Habilidades sociais - avaliação e intervenção; Gêmeas idênticas; Práticas educativas; Visual Impairment; Social skills; Identical twins; Mother s educative pratices and beliefs; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL